Assessment of COVID-19 Deaths in Botswana using the SIRD Model for the Period 2020 to 2022 - Lebotsamang Abidile (Journal of Epidemiology and Public Health, 2025)
Background: There is need for a development of a robust model framework for COVID-19 to help researchers simulate several virus transmission scenarios, assist in predicting the disease route as well as assess the effectiveness of mitigation measures. COVID-19 data with four compartmental groups, that is susceptible group, the infected group, the recovered group, and the deceased group was required to enable setting up a mathematical compartmental model called Susceptible-Infected-Recovered-Deceased (SIRD) for Botswana. This study aims to set up the SIRD model for COVID-19 in Botswana.Subjects and Method: The study took advantage of a retrospective cohort study carried out in Botswana specifically from a period ranging from 14th May 2020 to 3rd March 2022. The study population consisted of all persons who are susceptible to COVID-19 in Botswana and the sample size of this study was 2,397,240. Therefore, the variables of interest for this study were susceptible, infected, recovered as well as deceased persons. These were secondary data as reported by Botswana and recorded on the WHO website. Data for this study were analyzed using simulation methods specifically compartmental analysis.Results: COVID-19 will escalate at a very low transmission at an exponential growth rate of 0.11. The transmission of COVID-19 in Botswana will spread in the population and such spread may cause an epidemic (R0=1.13).Conclusion: The Ministry of Health and Wellness should ensure that there is slow relaxation of COVID-19 restrictions in order to avoid the reappearance of COVID-19. The Ministry of Health and Wellness should also strictly insist on COVID-19 adherence protocols mainly during the winter season as well as holidays.